1987
DOI: 10.3382/ps.0660442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cryptosporidiosis in Broiler Chickens

Abstract: Seven-day-old conventional broilers were inoculated either orally or intratracheally (IT) with 2.5 X 10(5), 5.0 X 10(5), or 2.0 X 10(6) oocysts of Cryptosporidium baileyi (32 birds for each dosage level per group; 192 birds total). Thirty-two birds served as unninoculated controls. Mean weekly weight gain and feed conversion were determined during a 5-week period. Carcass pigment was graded using a Roche Color Fan. Fecal oocysts were calculated from random cage samples 6, 8, 11, 13, 15, 18, 20, 22, and 25 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 15 publications
2
40
0
3
Order By: Relevance
“…C. parvum is now regarded as an economically important cause of neonatal diarrhea in calves and lambs (33)(34)(35)(36)(37)(38)(39). Another species, Cryptosporidium baileyi, is recognized as an important cause of respiratory disease in poultry and game birds (40)(41)(42)(43).…”
Section: Cryptosporidiosismentioning
confidence: 99%
“…C. parvum is now regarded as an economically important cause of neonatal diarrhea in calves and lambs (33)(34)(35)(36)(37)(38)(39). Another species, Cryptosporidium baileyi, is recognized as an important cause of respiratory disease in poultry and game birds (40)(41)(42)(43).…”
Section: Cryptosporidiosismentioning
confidence: 99%
“…The body weight gains of inoculated broiler chicks were lower than those of sham-inoculated controls (Ley, 1987); gross or microscopical lesions were not reported. In other studies, peroral inoculation of chickens and turkeys with oocysts of C. baileyi isolated from chickens resulted in parasitisation of epithelial cells of the bursa of Fabricius, ileum, large intestine and trachea Blagburn et al, 1987;Lindsay et al, 1987a, b, c). Other parts of small intestine were not infected and the birds were clinically normal.…”
Section: Infections Of the Gastro-intestinal Tractmentioning
confidence: 99%
“…The respiratory symptoms noted in the R0C4M15 group were certainly due to Cryptosporidium infection because the six chickens that died from days 17 to 39 during the respiratory disease showed massive infection of the respiratory tract by the parasite (Table 2 and Figure 2). C. baileyi inoculated alone by intratracheal or intraperitoneal route is able to induce respiratory disease and even mortality (Blagburn et al, 1987;Lindsay et al, 1987b;Lindsay & Blagburn, 1990), proving the primary respiratory disease potential of C. baileyi in the absence of other demonstrable pathogens (Blagburn et al, 1991). Respiratory disease following intratracheal inoculation at day 4 of C. baileyi oocysts in B13 chickens induced 20% mortality (data not shown).…”
Section: Table 3 Antibody Response Against C Baileyi Measured By Elmentioning
confidence: 99%
“…A decrease in humoral response to antigens such as sheep red blood cells and Brucella abortus (Rhee et al, 1998b,c), and in cell-mediated immunity, measured with the delayed hypersensitivity index (Blagburn et al, 1987), has also been induced by C. baileyi infections. It has therefore been suggested that attention should be given to the ability of C. baileyi-infected birds to respond to other agents such as viruses and intracellular bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation